2017
DOI: 10.1016/j.polymdegradstab.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ageing conditions on degradation of acrylonitrile butadiene rubber filled with heat-treated ZnO star-shaped particles in rapeseed biodiesel

Abstract: Effects of ageing conditions on degradation of acrylonitrile butadiene rubber filled with heattreated ZnO star-shaped particles in rapeseed biodiesel. Polymer degradation and stabilityAccess to the published version may require subscription. N.B. When citing this work, cite the original published paper. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Ultrasonication can effectively break the agglomeration and reduce particle size in fluid [25]. After the pretreatments, the C 60 nanoparticles were placed in the insulating oil and ultrasonically dispersed at 60 °C for at least 60 min (sx-sonic FS-1800N, maximum volume =3 L, ultrasonic peak output = 1800 W, frequency = 20 kHz, ultrasonic horn diameter = 20 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonication can effectively break the agglomeration and reduce particle size in fluid [25]. After the pretreatments, the C 60 nanoparticles were placed in the insulating oil and ultrasonically dispersed at 60 °C for at least 60 min (sx-sonic FS-1800N, maximum volume =3 L, ultrasonic peak output = 1800 W, frequency = 20 kHz, ultrasonic horn diameter = 20 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Another factor which could also affect the filler matrix interaction in polymer nanocomposites is the surface porosity of nanofillers. Akhlaghi et al, reported that heat-treated ZnO particles dispersed better than ZnO nanoparticles in acrylonitrile butadiene rubber (NBR) and promoted the curing of NBR [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aging and the performance improvement of polymers have become hot research topics [5,6,7]. Thermal aging is one of the major types of aging of insulation paper inside a transformer.…”
Section: Introductionmentioning
confidence: 99%